Zarządzanie procesowe w przedsiębiorstwie energetycznym na przykładzie Dolnośląskiej Spółki Gazownictwa - Węgrzyn, Adam (The Process Management in an Energy Enterprise on the Example of Lower Silesia Gas Company Ltd., 2009)
The process management is the key element in the time of modernizing the economy, creating the competitive market of energy and adapting the company functioning principles to requirements of EU directives. In the future, the only ones that have chances of surviving and further development are modernly managed companies. The Lower Silesia Gas Company Ltd. has established and implemented the Integrated System of Quality Management, Environment and Health and Safety, based on requirements of such norms as: PN-EN ISO 9001:2001, PN-EN ISO 14001:2005 as well as OHSAS 18001:2007 in which the process approach is highly promoted. The general criteria to identify the processes and procedures of the Integrated Management System have been these elements of the system that have the essential influence on the effectiveness of the company functioning, considering such essential aspects as gaining customers satisfaction and the ones that determine the repeatable, high quality and safety of the service completion. The purpose of this article is to describe the present structure of the process management in the constantly transformed gas distribution system operator. By watching the Company, before and after the division into two enterprises, where in one of the enterprise the core activity is gas distribution ,whereas in the second gas trade, it is possible to trace places of the division and their influence on the course of processes, to analyze problems one should deal with. The conclusions drawn on the basis of acquired experience show needs and directions of further improvement of processes and organization of the management system. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 221-229